Recovery of Gerd Disease in The Working Area of The Ciamis Health Center - Lilis Lismayanti; Rosmiati Rosmiati; Lutfi Qois; Ade Fitriani; Yanti Srinayanti (LPPM STIKes Muhammadiyah Ciamis, 2023)
GERD is a condition that often manifests as increased stomach acid, causing the mouth to become sour and bitter and burning or burning in the chest and solar plexus. This condition results in a psychological situation that ranges from anxiety to depression and is accompanied by physical symptoms such as shortness of breath, cold sweats, and if not treated will cause the patient's condition to get worse. Purpose: This study aims to describe the recovery of GERD in the Working Area of the Ciamis Health Center. Methods: This research was conducted using a survey method. This research was conducted by directly observing the research object and filling out the provided questionnaires. The population in this study were the people in the working area of the Ciamis Health Center who had a history of GERD, there were 57 respondents. Sampling was carried out using a total sampling technique, namely making the entire population as a research sample with a total of 57 people. Results: Out of 39 people who recovered from GERD, 25 people did not have GERD symptoms. Conclusion: Most of the people in the working area of the Ciamis Health Center recover from GERD.